Idiopathic Hypertrophic Pachymeningitis: Does Earlier Treatment Improve Outcome? - Emilia Rizzo; Ailsa Elizabeth Ritchie; Vinay Shivamurthy; Ata Siddiqui; Ming Lim (MDPI AG, 2020)
Background/goal: Hypertrophic pachymeningitis is a rare chronic inflammatory disorder characterized by marked fibrous thickening of the cerebral and/or spinal dura mater. This condition has largely been reported in adults, but there are very few reports in children. Methods: We describe a 14-year-old boy with idiopathic hypertrophic pachymeningitis, who presented with deteriorating vision on a background of severe headache. We evaluated pediatric cases of hypertrophic pachymeningitis and compared treatments and their relation to outcomes. Results: There are only eleven pediatric cases of hypertrophic pachymeningitis reported in the literature. In the patients treated with steroids either at presentation or subsequent relapses, a good response was reported. In the cases with delayed initiation of steroid treatment, this was often related to an incomplete recovery. In our patient, this delay may have contributed to his poor visual outcome. Conclusions: Early initiation of steroid treatment in children with idiopathic hypertrophic pachymeningitis may improve outcomes.